Gestão de resíduos de construção civil na zona urbana do município de Lagarto-SE: do diagnóstico a uma proposta de modelo gerencial - Prata, Valmir do Carmo (2013)
The buildings that are being renovated, enlarged or built considerably increased in the last decade, having, as consequence, the creation of civil construction waste (RCC) in large volume. These materials can cause serious environmental, sanitary, economic and social problems, once in several Brazilian cities, part of this waste is underhand put in places, such as wastelands, riverbanks and streets outlying neighborhoods. Thus it is believed that the adoption of concerned policies to manage the waste coming from civil construction can significantly minimize the social impacts and specially the environmental ones. In this perspective, considering that the municipality of Lagarto city, in the state of Sergipe, presents a similar situation, this study had as an objective to propose a managerial model l able to minimize the current problems associated to the management of construction waste (RCC) in the urban area of this municipality Therefore, it was done a bibliographical research, in order to meet and address the RCC management, and collecting data through field research. A Lot of data was collected in the City Hall of Lagarto in the system of licensing works such as in the collect department, in order to estimate the amount of RCC generated. Structured interviews were performed in this City Hall, in civil construction companies, and also with the RCC transporters and carters operating in the urban area. Aiming the spatialization of information, it was elaborated a mapping of irregular RCC disposal points after in loco identifying. Moreover, there was the characterization of these residues from collected samples from irregular deposition points. As a result, it was found there are 51 points of irregular RCC deposition in wastelands and margins of several roads and streets, and seven boot-outsides located on private acres in the urban area of Lagarto city and there aren t specializing companies for the collection of these residues; Most of the works, public or private, there aren t any RCC management plans and there are no points for legalized RCC deposition in small or large volumes. It Was estimated, for the daily urban area the generation of about 51.34 tons of RCC that revealed potential for such waste reuse and recycling after its performed characterization. The obtained results were used as input to the proposal drafting of a management model that aims to contribute to minimize problems concerning to RCC management in the urban area of Lagarto city.